Muon-induced background in the EDELWEISS dark matter search - Schmidt, B; Armengaud, E; Augier, C; Benoit, A; Berge, L; Bergmann, T; Bluemer, J; Bres, G; Broniatowski, A; Brudanin, V; Censier, B; Chapellier, M; et al. (2013)
A dedicated analysis of the muon-induced background in the EDELWEISS dark matter search has been performed on a data set acquired in 2009 and 2010. The total muon flux underground in the Laboratoire Souterrain de Modane (LSM) was measured to be Φμ=(5.4±0.2-0.9+0.5) muons/m 2/d. The modular design of the μ-veto system allows the reconstruction of the muon trajectory and hence the determination of the angular dependent muon flux in LSM. The results are in good agreement with both MC simulations and earlier measurements. Synchronization of the μ-veto system with the phonon and ionization signals of the Ge detector array allowed identification of muon-induced events. Rates for all muon-induced events Γμ=(0.172±0.012)evts/(kgd) and of WIMP-like events Γμ-n=0.008-0.004+0.005evts/(kgd) were extracted. After vetoing, the remaining rate of accepted muon-induced neutrons in the EDELWEISS-II dark matter search was determined to be Γirredμ- n<6·10-4evts/(kgd) at 90% C.L. Based on these results, the muon-induced background expectation for an anticipated exposure of 3000 kg d for EDELWEISS-III is N3000kgdμ-n<0.6 events. © 2013 Elsevier B.V. All rights reserved.